On-Board Diagnostic Tool menggunakan Mikrokontroler pada Kendaraan Listrik (EV) Terintegrasi dengan Speedometer - Zakiyah Amalia; Achsanul Khabib; Talifatim Machfuroh; Fica Aida Nadhifatul Aini; Diama Rizky Septiawan; Siti Duratun Nasiqiati Rosady; Ahsani Maulidina (Indonesian Society of Applied Science (ISAS), 2026)
Electric vehicles (EVs) are becoming a growing environmentally friendly transportation solution, but they still require an efficient and easily accessible vehicle condition monitoring system. Electric motorcycle users often experience difficulties in directly knowing the condition of the battery, motor, and drive system. Based on these problems, this study aims to develop an On-Board Diagnostic (OBD) system integrated with a speedometer to monitor the main parameters of two-wheeled electric vehicles in real-time. The research method includes designing a microcontroller-based system connected to a motor controller via UART and Controller Area Network (CAN) communication. The system is equipped with a DS3231 RTC module for time markers, an SD Card for data storage, and a 20x4 LCD to display voltage, current, power, temperature, and fault status (fault code). Testing was conducted on the Graha Merjosari Asri–Greenland at Tidar, Malang route, with speed variations between 0–45 km/h. The results show that the system is capable of detecting undervoltage conditions below 60 V, maintaining a stable maximum temperature of 41°C without overheating, and displaying vehicle data accurately and responsively. The developed OBD-speedometer system functions effectively as a portable and economical diagnostic tool for electric two-wheeled vehicles, with potential for development into an IoT-based intelligent monitoring system.